2017
DOI: 10.1177/0011392117736307
|View full text |Cite
|
Sign up to set email alerts
|

Access to healthcare for vulnerable migrant women in England: A human security approach

Abstract: The focus of this article is on post-migration entitlement and access to health security of women international migrants in England who are in vulnerable circumstances. Here ‘health security’ is defined as the protection of health within a broader public health context. The aim is to understand the factors underlying migrants’ vulnerabilities and how national and local health policies and practices respond in allowing or denying them rights to healthcare, thus impacting their ability to safeguard their health.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…Media coverage and government inquiry have focused on the disproportionate impact of the virus on the ethnic minority community without paying any closer attention to how the pandemic has affected men and women differently, apart from the first hand observation that men had recorded more fatalities than women (PHE 2020 , 10). There are also no specific policies or guidance on healthcare for vulnerable migrant women (Jayaweera 2018 , 277) adding to the difficulties in determining the pandemic’s full impact on migrant women. 4 However, by critiquing barriers to accessing healthcare from a feminist standpoint, we show that there are specific barriers for women aggravated by their race and cultural associations with race, or having migrant status and being subject to hostile immigration law.…”
Section: Barriers To Accessing Healthcare For Ethnic Minority and Migmentioning
confidence: 99%
See 1 more Smart Citation
“…Media coverage and government inquiry have focused on the disproportionate impact of the virus on the ethnic minority community without paying any closer attention to how the pandemic has affected men and women differently, apart from the first hand observation that men had recorded more fatalities than women (PHE 2020 , 10). There are also no specific policies or guidance on healthcare for vulnerable migrant women (Jayaweera 2018 , 277) adding to the difficulties in determining the pandemic’s full impact on migrant women. 4 However, by critiquing barriers to accessing healthcare from a feminist standpoint, we show that there are specific barriers for women aggravated by their race and cultural associations with race, or having migrant status and being subject to hostile immigration law.…”
Section: Barriers To Accessing Healthcare For Ethnic Minority and Migmentioning
confidence: 99%
“…The focus on the higher mortality rate from the virus for men worldwide somewhat eclipses the widening inequalities of gender and race (Flood et al 2020 , 6). Research has shown that ethnic minority and migrant women 1 are disproportionately affected by existing barriers to access to healthcare (Mirza and Sheridan 2003 ; Jayaweera 2018 ). These barriers have been generated and embedded by a system that overlooks the intersectional barriers raised by being an ethnic minority and/or a migrant 2 woman (Mirza 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…During this period, push and pull factors have changed dramatically, accompanied by new migration trends. Among others, migrant women are today slowly becoming the majority of migrants around the world and not just in the EU where it is estimated that women also make up a significant proportion of undocumented migrants (Jayaweera, 2018). The migration of women may be driven by individual factors, such as marital or reproductive status, education and skills, or by family or social factors like status or class (Fleury, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, migration can provide new opportunities for women either on their own or together with their spouses to improve their lives, escape oppressive social norms, and support children and other family members who are left behind. However, migration also exposes them to a series of vulnerable situations resulting from a precarious legal status, abusive working conditions, physical violence and health risks (de Leon Siantz, 2013;Fleury, 2016;Jayaweera, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation